Evaluating the efficiency of fog cooling for climate change adaptation in vulnerable groups: A case study of Daegu Metropolitan City. (1st June 2022) - Kim, Jaekyoung; Kang, Junsuk
Abstract: This study quantitatively analyzed the effect of fog cooling on temperature reduction and conducted an optimization study on the layout for planning a fog cooling system in the Daegu Metropolitan City. First, the design and verification of a single fog cooling unit was identified through an indoor experiment. Second, the temperature reduction effect of the installed fog cooling system was measured based on a sensor and verified through a finite volume method (FVM)-based computational fluid dynamics (CFD) analysis. Third, a numerical analysis of the optimal fog cooling arrangement was designed and performed in the Indongchon area. The temperature reduction design manual and model equations, which can be used by decision-makers, were analyzed through numerical analysis. The measured temperature reduction and simulation values had a high accuracy of R 2  ≥ 0.8. Based on the verified model, scenarios A–D were designed and analyzed according to the fog cooling arrangement. Scenario B, in which the fog cooling was arranged vertically to the wind direction, appeared to be the most efficient. In this case, the volume average temperature where fog cooling was installed could be reduced by up to 3.02 °C. It was also found that efficiency is higher when the fog cooling system is positioned at narrow intervals of ≤5 m than at wide intervals of ≥10 m, considering the wind direction. The results of this study can aid decision makers—including urban policymakers and planners—for estimating the potential extent of temperature reduction and increase in humidity by adopting fog cooling. Highlights: The use of fog cooling under temperature near 40 °C in Korea can reduce the temperature by about 3 °C (7%.) Cooling fog arrangement with an interval of 5 m installed perpendicular to wind direction is most effective. The temperature reduction effect of fog cooling is greater at 1 m from the ground, the sensible height of the vulnerable groups, than 1.5 m. A fog cooling system having an interval of 5 m is most effective to reduce heatwave.